FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDINGS PERUSAHAAN DI BURSA EFEK INDONESIA - Suherman, Suherman (Jurnal Manajemen, 2017)
The purpose of this study is to examine determinants of cash holdings of non-financial firms listed on Indonesia Stock Exchange between 2012 and 2015. Sample of this research covers 328 firms (1312 observations). This research employs fixed effect model. The results show that net working capital and sales growth have positive effects on cash holding, while firm size has negative effect. Cash flow, cash flow variability, cash conversion cycle, liquidity, leverage do not affect the cash holdings.